The Relationship Between Psychological Well-Being and Self-Care Behavior In The Elderly With Hypertension - Fina Chalimatus Sa'adah,; Kusumawardani, Lita Heni; Anam, Akhyarul (Journal of Islamic Nursing, 2025)
Older adults are at risk of developing degenerative diseases such as coronary heart disease, hypertension, diabetes mellitus, and others. One of the problems that many older adults suffer from is hypertension. This study aimed to analyze the relationship between psychological well-being and self-care behavior in the elderly with hypertension. This quantitative research method used a cross-sectional design to analyze correlations with the Somer'd gamma test. One hundred seven elderly respondents with hypertension in Notog Village, Patikraja District, Banyumas Regency, used nonprobability sampling techniques. Data were taken using the Psychological Well-Being Scale (PWBS) and Hypertension Self Profile (HBP-SCP): Behavior Scale questionnaires. The research showed that most respondents had a moderate level of psychological well-being of 57.9% and a moderate level of hypertension self-care behavior of 64.5%. The results of this study showed that there was a significant relationship between psychological well-being and hypertension self-care behavior (p value=<0.001, p<0.05) with a moderate level of correlation (coefficient r=0.477). There was a significant relationship between psychological well-being and self-care behavior in older adults with hypertension.